GPER limits adverse changes to Ca2+ signalling and arrhythmogenic activity in ovariectomised guinea pig cardiomyocytes - Francis, Alice J.; Firth, Jahn M.; Sanchez-Alonso, Jose L.; Gorelik, Julia; MacLeod, Kenneth T. (Frontiers in Physiology, 2022)
Abstract Background: The increased risk of post-menopausal women developing abnormalities of heart function emphasises the requirement to understand the effect of declining oestrogen levels on cardiac electrophysiology and structure, and investigate possible therapeutic targets, namely the G protein-coupled oestrogen receptor 1 (GPER). Methods: Female guinea pigs underwent sham or ovariectomy (OVx) surgeries. Cardiomyocytes were isolated 150-days post-operatively. Membrane structure was assessed using di-8-ANEPPs staining and scanning ion conductance microscopy. Immunohistological staining determined the localisation of oestrogen receptors. The effect of GPER activation on excitation-contraction coupling mechanisms were assessed using electrophysiological and fluorescence techniques. Downstream signalling proteins were investigated by western blot. Results: Immunostaining confirmed the presence of nuclear oestrogen receptors and GPER, the latter prominently localised to the peri-nuclear region and having a clear striated pattern elsewhere in the cells. Following OVx, GPER expression increased and its activation reduced Ca2+ transient amplitude (by 40%) and sarcomere shortening (by 32%). In these cells, GPER activation reduced abnormal spontaneous Ca2+ activity, shortened action potential duration and limited drug-induced early after-depolarisation formation. Conclusions: In an animal species with comparable steroidogenesis and cardiac physiology to humans, we show the expression and localisation of all three oestrogen receptors in cardiac myocytes. We found that following oestrogen withdrawal, GPER expression increased and its activation limited arrhythmogenic behaviours in this low oestrogen state, indicating a potential cardioprotective role of this receptor in post-menopausal women.